THE EFFECTIVENESS OF GO-LAB BASED INQUIRY LEARNING SPACE (ILS) AS MEDIA ON SCIENCE SUBJECT FOR JUNIOR HIGH SCHOOL IN INDONESIA - Faresta, Rangga Alif; Suhardi, Rizal M.; Safana, Mega (Jurnal Tatsqif, 2024)
A PISA survey in 2018 showed that Indonesian students underperformed in science results. Consequently, the rate of scientific concepts and literacy is low, especially in junior high school grades. However, Inquiry-based learning can be used to improve science concepts and literacy. One of the science tools to improve students’ science concepts and literacy-based inquiry is Go-Labs. The Go-Lab provides students with an Inquiry Learning Space feature. This investigation aims to find out the effectiveness of the Go-Lab-based Inquiry Learning Space (ILS) as a medium for teaching science subjects to junior high school students in Indonesia. This systematic literature method was used to provide evidence from 21 of the literature related to Go-Lab and science literacy. This provided an overview of current knowledge of the Go-Lab's effectiveness on students’ science concepts and literacy. The result is the Go-Lab can be used as an alternative media for teachers in science teaching to assist students in improving their ability in science. Go-Lab can benefit students by improving their ability in scientific concepts and improve their scientific literacy. This is because the Go-Lab is embedded with an Inquiry-based learning approach, the effectiveness of Inquiry Learning Space (ILS) in Go-Lab, and the Go-Lab’s ecosystem supports the science teaching process. The implication of this investigation is to provide alternative mediums in science teaching to engage students with scientific concepts. Hence, the Go-Lab can be used as an alternative media for teachers in science teaching to assist students in improving their ability in science.